A SAXS study of the pore structure evolution in biochar during gasification in H2O, CO2 and H2O/CO2 - Liu, Y.; Paskevicius, Mark; Sofianos, M.V.; Parkinson, G.; Wang, Shuai; Li, Chun-Zhu (ELSEVIER SCI LTD, 2021)
Gasification of biomass allows for its efficient utilisation as a renewable fuel through syngas production. This work presents the different effects of gasifying agents (H2O, CO2 and H2O/CO2) on the pore structure evolution in biochar during gasification. The effects of temperature (700, 800 and 900 °C) and biomass particle size (up to 5.6 mm) were also studied. The pore structure of biochar was characterized using synchrotron small angle X-ray scattering (SAXS). The pore development in biochar during gasification in H2O/CO2 was close to that in H2O. Carbon removal is more selective in CO2 than H2O and the derived biochar displayed pore fractal features, whereas the biochars gasified in H2O and H2O/CO2 exhibited a surface fractal network due to the less selective carbon removal in the presence of H2O. The pore structure development produced by various gasifying agents was paralleled by the evolution of the aromatic structures characterized by Raman spectroscopy. The different pore structure features result from the different reactivity of carbon sites with H2O and CO2, which can be attributed to the different amounts of O-containing groups in biochar, as well as the different reactivity of H2O and CO2. Increasing temperature reduced the differences in pore structure between biochars gasified in H2O and CO2. Biomass particle size had little impact on the pore structure of biochar.